2018
DOI: 10.3390/buildings8120172
|View full text |Cite
|
Sign up to set email alerts
|

Energetic, Cost, and Comfort Performance of a Nearly-Zero Energy Building Including Rule-Based Control of Four Sources of Energy Flexibility

Abstract: A focal point of ongoing research is matching the energy demand in the built environment to the energy supply from onsite generation, to maximize the self-consumption, and from the energy grids, to lower energy costs and reduce peak loads on the system. Energy flexibility addresses this task by modulating the energy demand in a building according to dynamic criteria such as electricity prices or onsite generation. This study addresses the potential of building performance simulation with real time rule-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similarly, it has been found that 14% of the energy demand and cost can be reduced in commercial buildings by implementing energy flexibility for heating and cooling [15]. An experimental study shows that the energy flexibility action can reduce the energy cost by 4% depending on the flexibility options available [16]. Integrating solar energy and energy storage such as phase change materials [17], batteries or tanks [16] can also be used for better flexibility.…”
Section: Energy Flexibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it has been found that 14% of the energy demand and cost can be reduced in commercial buildings by implementing energy flexibility for heating and cooling [15]. An experimental study shows that the energy flexibility action can reduce the energy cost by 4% depending on the flexibility options available [16]. Integrating solar energy and energy storage such as phase change materials [17], batteries or tanks [16] can also be used for better flexibility.…”
Section: Energy Flexibilitymentioning
confidence: 99%
“…An experimental study shows that the energy flexibility action can reduce the energy cost by 4% depending on the flexibility options available [16]. Integrating solar energy and energy storage such as phase change materials [17], batteries or tanks [16] can also be used for better flexibility. All the studies show that further analysis is needed to identify the benefits of energy flexibility in terms of cost and flexibility.…”
Section: Energy Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Perera and Skeie [14] presented a set of rule-based controllers that set setpoint and setback temperatures based on predefined occupancy schedules. Delgado et al [15] provided a rule-based controller for maximizing self-consumption and reducing costs. Rule-based approaches, however, do not take any future information (e.g., future price, future hot water usage) into account, and therefore their efficacy is limited [16].…”
Section: Literature Reviewmentioning
confidence: 99%